Development of Short Story Appreciation TextbookUsing Contextual Approach at Junior Secondary Schools - Susilowati, Dwi; Nurkamto, Prof. Dr. Joko; Waluyo, Prof. Dr. Herman J.; Suwandi, Prof.Dr. Sarwiji; Andayani, Prof. Dr. (IJRDO- Journal of Educational Research, 2017)
Short story appreciation learning enables the students to reach the language level of appreciation, expression, and creation. In short story learning, the aspect of appreciation has not been emphasized. It happens due to unfamiliarity with various kindsof short story. Besides, the learning process is only dominated by teachers due to the limited number of short story appreciation textbooks.This research applied the R&D method with the following stages: (1)exploration; (2) model development; (3) model testing; and (4) dissemination. Through the stages, a short stoy appreciation textbook for Junior Secondary Schools was designed.The model development was done through the stages of textbook drafting, limited textbook testing, extended textbook testing, and workshop with expert judgement.The designed textbook includedconstructivism, inquiry, learning community, inquiry exercise, modeling, reflection and autehtic assessment.The result of this research shows that in the learning process of short story appreciation,a reliable textbookwas required.The textbook was experimentally reliable and significant. It was also acceptable in the dissemination stage.